Pengasuhan Anak pada Keluarga dengan Orang Tua Bekerja: Studi Kasus Kabupaten Bekasi Parenting in Working Parents Families: Case Study Bekasi Regency: CASE STUDY BEKASI REGENCY - Husnah, Wabilia; Novianafari, Ifa Prasetya; Sholihat, Siti `Ilmawati (LIPI Press, 2023)
The involvement of both parents in parenting (co-parenting) has positive implications for children’s growth and development, including in families with working mothers. The growing number of working women, one of whom lives in Bekasi Regency, emphasizes the importance of balancing the responsibilities of both parents in raising children. Unfortunately, fathers’ involvement in parenting is still limited. This study examines how the division of parenting responsibilities works in working parents families from case study research on families with working mothers in Bekasi Regency, the research focuses on the positions of mothers and fathers in the distribution of parenting roles, the challenges of involving fathers in parenting, and evaluates that encourage father involvement in parenting. According to the intersectionality theory, even though father involvement is increasing, there is an imbalance in the distribution of parenting roles. This inequality is caused by the intersection of many factors, like socio-political, cultural, economic, educational, and religious interpretation factors. Thus, intervention efforts are needed in these various factors to maximize the role of fathers in parenting, for the realization of Indonesia Emas 2045.